Meningkatkan Loyalitas Nasabah melalui Transformasi Digital dan Kepuasan Nasabah di PT Prudential CBD Medan Polonia - Rambe, Aqli Nadzhari; Imsar, Imsar (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The rapid shift from conventional insurance services to digital platforms poses significant challenges for Sharia-based insurance companies in maintaining customer loyalty. This study aims to examine the effect of digital transformation on customer loyalty, with customer satisfaction as a mediating variable, in the context of PT Prudential Syariah, Medan Polonia CBD. Using a quantitative explanatory research design, data were collected through structured questionnaires from 376 purposively selected customers. Variables measured include digital transformation (independent), customer satisfaction (mediator), and customer loyalty (dependent). Data analysis employed linear regression and Sobel test using SPSS 25. Results indicate that digital transformation has a positive and significant impact on both customer satisfaction and loyalty. Furthermore, customer satisfaction positively and significantly influences customer loyalty, and it mediates the relationship between digital transformation and loyalty. These findings suggest that enhancing digital service features such as user-friendly applications, efficient claims processes, and real-time policy management can foster higher satisfaction levels, which in turn strengthen long-term customer commitment. Practically, insurance companies, particularly in the Sharia sector, should prioritize digital innovation to remain competitive and build sustainable customer relationships in the digital era.